Individual Religiosity, Spirituality, Humility and Anxiety as Predictors of Athlete's Life Satisfaction - AYTEN, ALİ; BAKIR, RAHİME EYMEN (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2021)
Numerous factors have an impact on life satisfaction on individuals. While religiosity, spirituality and values are world-view building, anxiety is related to the individual's perception of life conditions. In this context, this article's main aim is to examine the predictive roles of individual religiosity, spirituality, humility and anxiety tendencies on the life satisfaction of martial arts' athletes. The study sample consists of 251 athletes whose average sports age is seven years, taekwondo, karate-do and kickboxing from all over Turkey. In order to collect data; a questionnaire consisting of Personal Information Form, Spirituality Assessment, Individual Religiosity Inventory, The Humility Scale, Generalized Anxiety Scale and Satisfaction with Life Scale has been utilized. This research is a quantitative study conducted in according to the relational survey model. Findings indicated that individual religiosity, spirituality and anxiety are significant predictors of athlete's life satisfaction.
Keywords: Psychology of Religion; Positive Psychology; Religiosity; Sport; Martial Arts; MENTAL-HEALTH; HAPPINESS